Invited Review Paper in Commemoration of Over 50 Years of Oxidation of Metals: Current Aspects of Deposit-Induced Corrosion - Meier, G. H. (High temperature corrosion of materials, 2022)
Alloys and coatings used in high temperature applications are often subject to surface degradation influenced by the presence of deposits. Typical examples are fireside corrosion in coal-fired boilers and hot corrosion of blades and vanes in the hot sections of gas turbines. Depending on the source, deposit compositions may occur in a wide range from primarily sulfate to primarily oxide and various combinations of the two. There does not seem to be evidence of severe corrosion caused by gaseous Na 2 SO 4 . Generally, severe corrosion occurs when the deposits are liquid. However, significant corrosion has been observed in some cases with deposits, which are nominally solid. Corrosion is often caused by liquid deposits, in which negative oxide solubility gradients for alloy components are established across the deposits by rapid interface reactions. Hot corrosion can occur at temperatures near 700 °C by a variety of mechanisms if a phase which allows rapid transport is formed. This includes compounds such as Na 2 MoO 4 (even in atmospheres without SO 3 ), MSO 4 –Na 2 SO 4 solutions or metastable nanostructured phases. Calling all corrosion in this temperature regime “Type II” can be misleading with regard to mechanism. There are similarities in the underlying mechanisms of some forms of hot corrosion in the 700 °C range and fireside corrosion in that they involve synergistic fluxing. The corrosive species responsible for fireside corrosion of ferrous alloys is a liquid (Na,K) 2 SO 4 –Fe 2 (SO 4 ) 3 solution and not alkali iron trisulfate. The propagation mechanism involves a synergistic dissolution process of protective Cr 2 O 3 and Fe 2 O 3 . Terms such as “Type I,” “Type II” and “gas-phase-induced acidic fluxing” should be used with care in describing mechanisms of deposit-induced corrosion.